The Effect of Nursing Education on Pain Levels in Postoperative Patients - Eppy Setyowati; Justinho Soares; Sulis Setiyanti; Bayu Rizky Pratama (Indonesian Journal of Global Health Research, 2026)
Postoperative pain is one of the most common problems experienced by patients following surgical procedures. Nursing education is a non-pharmacological intervention that may help reduce pain levels. This study aimed to determine the effect of nursing education on postoperative patients' pain levels. A quantitative research design with two independent groups was employed, consisting of an education group and a non-education group, with a total of 30 respondents. Data were collected through direct measurement of postoperative pain intensity using the Numeric Rating Scale (NRS) at baseline (pre-test) and after the intervention (post-test) in both the intervention and control groups.The data were analyzed using both parametric (Independent t-test) and non-parametric (Mann–Whitney U test). The results showed a significant value of p < 0.05 in both tests, indicating a significant difference between the two groups. Nursing education was found to be effective in reducing pain levels among postoperative patients.